THE ROLE OF THE 9TH-CENTURY TERMIZ SCHOLARLY MILIEU IN THE HANAFI JURISPRUDENCE AND HADITH TRADITION: A COMPARATIVE ANALYSIS OF THE JURISPRUDENTIAL-METHODOLOGICAL VIEWS OF AL-HAKIM AL-TIRMIDHI AND IMAM AL-TIRMIDHI - Ibragimova, Manzura (Oriental Journal of History, Politics and Law, 2026)
This article examines the role and distinct characteristics of the 9th-century Termiz school of Islamic learning in the development of Hanafi jurisprudence (fiqh) and Hadith traditions. The central focus of the study is a comparative analysis of the scholarly legacies of two paramount figures of this intellectual circle: Imam al-Tirmidhi and Al-Hakim al-Tirmidhi. The research contrasts Imam al-Tirmidhi's contributions to systematizing the esoteric (zahir/legal) sciences, particularly comparative fiqh and Hadith methodology, with Al-Hakim al-Tirmidhi's approach to uncovering the philosophical and spiritual dimensions of Islamic law (maqasid al-shari'ah) through esoteric (batin/mystical) wisdom (hikmah). The author argues that despite their methodological differences, the perspectives of these two scholars were not contradictory but rather formed a perfect synthesis that balanced law and spirituality within the Termiz academic milieu.